2001
DOI: 10.2466/pms.2001.92.3c.1039
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Instruction for Correcting Errors versus Such Instructions Plus Videotape Replay on Learning the Overhand Throw

Abstract: The influence of two methods of providing information to women, ages 19 to 22 years who were novices and learning the overhand throw with the nondominant arm, was examined. One group received verbal information on correcting errors, and a second group received the same information immediately prior to viewing a videotaped replay of a just completed throw. Performance was assessed quantitatively with respect to outcome (distance thrown) and qualitatively with respect to throwing form as measured on a 7-point ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
3
1
1
Order By: Relevance
“…With an additional cue (visual) added, the shooting form should improve more than that by verbal cueing per se. This finding diverts from some studies which found that experts' modeling is of no use in assisting learning, to the contrary it will interfere learning (Schmidt & Wrisberg, 2008) and video replay may be redundant and unnecessary (Kernodle et al, 2001). It might be because the single-handed shooting form was not complicated to the participants, thus the use of verbal cues has already provided sufficient information for the participants to retain the movement form of free throw shooting.…”
Section: Discussioncontrasting
confidence: 56%
“…With an additional cue (visual) added, the shooting form should improve more than that by verbal cueing per se. This finding diverts from some studies which found that experts' modeling is of no use in assisting learning, to the contrary it will interfere learning (Schmidt & Wrisberg, 2008) and video replay may be redundant and unnecessary (Kernodle et al, 2001). It might be because the single-handed shooting form was not complicated to the participants, thus the use of verbal cues has already provided sufficient information for the participants to retain the movement form of free throw shooting.…”
Section: Discussioncontrasting
confidence: 56%
“…Instead, it seems plausible to suggest any encoding and subsequent learning benefits that can be derived from error estimation are diminished in these practice conditions. For example, KR may be requested (or provided) on a trial where it only provides information that is redundant with response-produced feedback (e.g., Magill et al, 1991 ; Buekers et al, 1992 ; Hale and Franks, 1998 ; Kernodle et al, 2001 ). Alternatively, KR may not be requested (or provided) for a trial where it would have provided valuable information to strengthen one’s memory representation.…”
Section: Discussionmentioning
confidence: 99%
“…These results may have occurred because the participants were able to process the information without becoming overwhelmed and were therefore able to use an internal source of information more effectively. Kernodle et al (2001) conducted an experiment on learning an overarm throw that examined the effectiveness of verbal instructions for correcting errors versus verbal instructions in addition to watching a videotape replay. The only significant difference was that the rated throwing form for retention by the group receiving verbal instruction alone had a higher mean rating than that of the group that was given the combined information.…”
Section: Discussionmentioning
confidence: 99%